Determinants of antenatal care utilization among pregnant women: A qualitative study - Novica Ariyanti Putri; Sova Evie; Hasni Hasni; Saman Saman; Enggar Enggar (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Antenatal care (ANC) plays a critical role in preventing pregnancy-related complications and improving maternal and neonatal outcomes. Despite expanded maternal health services, inadequate utilization of ANC remains a significant challenge in many settings. Understanding the contextual factors that influence women’s decisions to seek antenatal services is essential for improving maternal healthcare delivery. This study aimed to explore the determinants influencing antenatal care utilization among pregnant women. Research Methodology: This study employed a qualitative exploratory design. Data were collected through in-depth interviews with pregnant women who had experience accessing antenatal services. Participants were selected using purposive sampling to ensure inclusion of individuals with relevant experiences. Data collection continued until thematic saturation was achieved. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis to identify patterns and themes related to antenatal care utilization. Results: The analysis identified four major themes influencing antenatal care utilization: maternal knowledge and awareness of pregnancy care, accessibility of health services, family support and decision-making dynamics, and socio-cultural beliefs regarding pregnancy. Women who had better knowledge of antenatal care benefits were more motivated to attend routine visits. However, structural barriers such as distance to health facilities, transportation constraints, and long waiting times sometimes limited-service utilization. Family encouragement, particularly from husbands, facilitated antenatal care attendance, while cultural perceptions that pregnancy is a natural process occasionally reduced the perceived need for routine check-ups. Conclusion: Antenatal care utilization is shaped by a complex interaction of individual, social, and health system factors. Strengthening maternal health education, improving accessibility of primary healthcare services, and promoting family involvement in pregnancy care are essential strategies to increase ANC utilization. Policies and interventions addressing these multidimensional determinants are necessary to improve maternal health outcomes.